(untitled) (Global Journal of Science Frontier Research, 2023)
Scanning electron microscopy SEM is one of the popular methods for imaging the microstructure and morphology of materials In an SEM a low-energy electron beam hits the material and scans the surface of the sample As the beam reaches and enters the material various interactions occur that result in the emission of photons and electrons from or near the sample surface To produce an image the received signal produced by the electron-sample interaction is detected with different types of detectors depending on the her SEM mode used There are various his SEM modes for characterization of materials including biomaterials B X-ray imaging secondary electron imaging backscattered electron imaging electron channeling Auger electron microscopy